VALIDASI PENGEMBANGAN MULTIMEDIA INTERAKTIF MEDAN MAGNET MENGGUNAKAN ADOBE FLASH SEBAGAI MEDIA PEMBELAJARAN FISIKA KELAS 12 SMA - Ririn Sabani; M. Rahmad '; M. Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to design and build interactive multimedia on the magnetic field’s topic using adobe flash as a physics learning mediafor twelfth grade in senior high school. The type of product is validation of multimedia interaktif. This research was a R&D research using ADDIE models. The data was needed on this research was the validation assessment score given by the validator of multimedia learning form validation and evaluation sheets with using descriptive analysis techniques by converting the data into quantitative data, that was expressed in the form of a number with a certain interval. Validator consists of 4 people as a experts construct and 3 people as a expert user that given the score by the aspects of the design, pedagogy, learning content, and users. Validation was done two times, the first validation was repairs and second validation was the votes. The final results of the validation assessment of experts construct was 3.49 with categorized as very high and ratings obtained from expert users was 3.59 categorized as very high. Based on these results, we can conclude that the interactive multimedia using adobe flash as a physics learning media for twelfth grade in senior high school declared valid and eligible for use in the process of learning and teaching.Kata Kunci: Interactive Multimedia, Adobe Flash, Magnetic Field, Validation